Development and validation of a reversed-phase HPLC method for the determination of lisinopril and gliclazide in pharmaceuticals - ŞENKARDEŞ, SEVİL; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ; UĞURLU, TİMUÇİN (MARMARA UNIV, FAC PHARMACY, 2017)
The aim of the present study was to develop and validate a High-Performance Liquid Chromatography (HPLC) method for the determination of lisinopril and gliclazide. The method was developed on Zorbax C-8 analytical column (4.6x250 mm; 5 mu m) by isocratic elution with a flow rate of 1.0 mL/min and injection volume of 25 mu l. The mobile phase composition was methanol: water (65:35 v/v, pH adjusted to 3.0 triethylamineorthophosphoric acid buffer) and the retention time was found to be 2.883 and 7.456 min for lisinopril and gliclazide, respectively. The developed method was found to be linear in the concentration range of 5-20 mu g/mL for lisinopril and 15-60 mu g/mL for gliclazide. The method was validated for linearity, accuracy, precision, LOD and LOQ. This developed procedure was succesfully applied conveniently for the analysis of lisinopril and gliclazide in pharmaceutical preparations.
Keywords: Combined dosage forms; gliclazide; lisinopril; RP-HPLC; method validation; DIABETES-MELLITUS; SPECTROPHOTOMETRY; PHARMACOLOGY; MANAGEMENT; EFFICACY